Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1978957
|View full text |Cite
|
Sign up to set email alerts
|

Augmented reality flavors

Abstract: The main contribution of this paper is to realize computer generated augmented flavors and establish a method to integrate gustatory information into computer human interactions. There are several reasons for the scarcity of research on gustatory information. One reason is that taste sensations are affected by a number of factors, such as vision, olfaction and memories. This produces a complex cognition mechanism for a user's gustatory sensation, and makes it difficult to build up a gustatory display which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(27 citation statements)
references
References 27 publications
0
26
0
1
Order By: Relevance
“…I think the electrophoresis approach to taste display is unique, and this idea is different from any other method that has been proposed for gustatory interfaces [21]. The gustatory display in [12] is a pseudo display that presents the desired tastes by means of a cross-modal effect elicited by visual and olfactory stimuli. Because the taste display has a simple structure, it can be built and validated with the information described in this paper, which I encourage the readers to try.…”
Section: Discussionmentioning
confidence: 99%
“…I think the electrophoresis approach to taste display is unique, and this idea is different from any other method that has been proposed for gustatory interfaces [21]. The gustatory display in [12] is a pseudo display that presents the desired tastes by means of a cross-modal effect elicited by visual and olfactory stimuli. Because the taste display has a simple structure, it can be built and validated with the information described in this paper, which I encourage the readers to try.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies have focused on custom-made devices for the isolated usage of specific secondary cues. These cues include spatial sound [36]- [39], low-frequency sound [37], [40], [41], specific physical cues related to exertion [42], smell [43], [44] gustation [45], [46], and wind [47], [48]. While handling multisensory cues, our study is partially affected by cross-modal effects.…”
Section: Terminology and Related Workmentioning
confidence: 99%
“…For instance, a study showed that tactile, olfactory and auditory cues produce more sense of presence and memory than just adding visual details in the scene [27]. In other example, Narumi et al [71] employed different scents to create the illusion of flavors in augmented reality.…”
Section: Smell As Interaction Modalitymentioning
confidence: 99%